Meningkatkan Sistem Kekebalan Tubuh Terhadap Infeksi Saluran Pernapasan Melalui Vaksinasi - mulya, widya -; Mulyana, Wiwik; Sari, Iin Pratama; yuliana, Lina (Program Studi D4 K3 Universitas Balikpapan, 2023)
Respiratory tract and lung infections are one of the main causes of morbidity and mortality worldwide. The Global Burden of Disease Study revealed that deaths related to lower respiratory tract infections, especially infants and young children, are a high-risk group, in Indonesia, based on the 2020 Indonesia Health Profile, it reached 34.8%, moreover there is the 2019 coronavirus disease (CoronaVirus Disease 19/COVID-19). 19) which was declared a pandemic by the World Health Organization on March 11, 2020. Until the end of April 2021, COVID-19 had infected at least 1.69 million people in Indonesia. The virus that causes COVID-19 is a virus that has a genome in the form of single-stranded RNA, this virus can also mutate, even though it is a virus with an RNA genome, the mutation rate of the virus that causes COVID-19 is not as fast as viruses with other RNA genomes such as the Influenza virus, this is because in the virus that causes COVID-19 there is a mutation repair mechanism that is not present in the Influenza virus. There are three types of influenza vaccines, namely Inactivated Influenza Vaccine (IIV), Recombinant Influenza Vaccine (RIV), and Live Attenuated Influenza Vaccine (LAIV). Currently, there are several vaccine platforms used to develop the SARS-CoV-2 vaccine, namely live attenuated vaccines, inactivated whole-virus vaccines, subunit vaccines, virus-like particle (VLP) vaccines, mRNA-based vaccines, DNA-based vaccines, and virus vector-based. Vaccines aim to provide acquired immunity and create immunity to cause disease. Fully vaccinated people are less likely to be infected or to be asymptomatic and less likely to spread the virus to others. Herd immunity also protects individuals who are not vaccinated (such as newborns and those with contraindications to the vaccine). Keywords: Immune System, Respiratory Tract Infection, Vaccination.